Accent Choices of English Majors in the Netherlands: Patterns and Motivations - Gezina Christien Dorothé Huttenga; Dick Smakman (Journal of Linguistics and Language Teaching)
This paper investigated the accent choices and realisations of first-year students of English in the Netherlands and linked these choices to the social identity, or persona, they wished to express in English. Further, it was investigated how important students felt identity expression was relative to other criteria in their pursuit of a certain accent. This group gives us an impression of the norms that future teachers may apply in their classes. Most (70) of the survey participants preferred to follow the Standard British English (Received Pronunciation) articulation model, while a reasonable group (29) were more inclined towards more Americanised and international accents. Interviews demonstrated that students held traditional connotations toward accents of English: Received Pronunciation indexed tradition and formality and related characteristics while general American indexed dynamism, internationalism, and related characteristics. Identity expression was relatively low on the agenda of these students. The sound file analysis revealed students were not consistent in applying their stated RP preference when they actually speak. They mixed their accent not only with their L1 but also with American English, possibly below the threshold of awareness. The results show that this particular group distinguished clearly between school norms and real-life norms. Our suggestion is that this distinction deserves more attention in teaching so that students become better prepared for real-life communication and become mainly concerned about international and intercultural intelligibility. L1 influences may be embraced as being natural and not in need of suppressing if they do not hinder intelligibility.